1991
DOI: 10.1530/acta.0.1240425
|View full text |Cite
|
Sign up to set email alerts
|

Production of corticosterone and testosterone in scorbutic mutant rats: difference of in vivo production between adrenal gland and testis

Abstract: Abstract. Effects of deficiency in ascorbic acid on in vivo production of corticosterone and testosterone were examined using a mutant strain of rats unable to synthesize ascorbic acid. The adrenal weight of scorbutic rats was larger, and corticosterone levels in plasma and adrenal tissues were higher than those of ascorbic acid-supplied (ascorbutic) rats. Acute and chronic stimulation with ACTH increased corticosterone levels in both ascorbutic and scorbutic rats. In contrast, weights of seminal vesicles and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The relationship between the level of ascorbic acid and testosterone of –VC mice has not been determined, but no significant change in basal plasma levels of testosterone has been reported in mutant rats unable to synthesize ascorbic acid (Ito et al ., 1992). Fukuda et al . (1991) also demonstrated that ascorbic acid is not essential for the synthesis of steroid hormones in scorbutic mutant rats.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the level of ascorbic acid and testosterone of –VC mice has not been determined, but no significant change in basal plasma levels of testosterone has been reported in mutant rats unable to synthesize ascorbic acid (Ito et al ., 1992). Fukuda et al . (1991) also demonstrated that ascorbic acid is not essential for the synthesis of steroid hormones in scorbutic mutant rats.…”
Section: Discussionmentioning
confidence: 99%
“…At the intestinal level there is probably a competitive inhibition of ascorbate uptake by oestradiol, which may explain a decrease in circulating ascorbate during steroid intake (Kuo & Lin 1998). Fukuda, Ito, Hirota, Tsuji & Mori (1991) argued that ascorbate is not required for steroid hormone (testosterone) synthesis as they observed an 8‐ to 14‐fold increase in circulating testosterone and a fivefold increase in testicular testosterone after human chorionic gonadotropin stimulation in scorbutic rats. In an accompanying study, the same research group (Ito, Tsujki, Terada, Miyano & Mori 1992) reinforced that conclusion by providing data on undetectable ascorbate concentrations in liver.…”
Section: Steroidogenesis (Fig 3)mentioning
confidence: 99%
“…Previously we reported using the ODS rats that a deficiency of AsA resulted in a difference in vivo production of steroids between the adrenal cortex and the testis (Fukuda et al, 1991). Corticosterone (C) levels in plasma and adrenal tissues of scorbutic rats were higher than those in ascorbutic rats.…”
Section: Introductionmentioning
confidence: 95%
“…AsA has been considered to play an important role in the production and secretion of steroid hormones (Levine and Monta, 1958). However, numerous studies, mostly in vitro using the adrenal tissues, have shown complicated results concerning the role of AsA in the steroidogenesis (Tsuji et aI,, 1989;Tsuji et al, 1990;Ito et al, 1990;Fukuda et al, 1990;Fukuda et al, 1991): AsA either stimulates some steroidogenic enzymes, inhibits other enzymes, or has no effect on others according to enzymes examined and conditions employed. The in vivo study seems more informative on the physiological role of AsA than the in vitro study.…”
Section: Introductionmentioning
confidence: 99%